Islamic Ecotheology, Green Radicalism, and SDGs: Ecological Ideology in the Political Islam Movement in Indonesia - Saeful Anwar; Suttrisno; Muhammad Hanif bin Ali (Profetika: Jurnal Studi Islam, 2025)
Objectives: This study aims to examine how Islamic ecotheology is constructed within political Islamic movements in Indonesia, particularly focusing on the rise of green radicalism. It explores how Qur’anic ecological verses are politicized by radical groups to criticize democracy and promote the caliphate system. Theoretical framework: The study uses Althusser’s ideology theory and Fairclough’s critical discourse analysis to analyze how ecological narratives are politicized. It also introduces the Radical Ideological Ecotheological (EIR) Model, combining maqāṣid al-sharī‘ah and SDGs frameworks. Literature review: A systematic review of 42 articles highlights the politicization of Qur’anic ecological verses by political groups and the intersection of Islamic ecotheology with global sustainability discussions. Method: The study employs a systematic literature review (SLR) of 42 articles, using Althusser’s ideology theory and Fairclough’s critical discourse analysis to analyze how radical movements utilize ecological narratives. Result: Radical groups selectively use Qur’anic ecological verses to criticize democracy and advocate for a caliphate. The study introduces the Radical Ideological Ecotheological (EIR) Model, which integrates Islamic law objectives (maqāṣid al-sharī‘ah) with the SDGs framework. Implications: The study suggests practical ways to strengthen ecological literacy in Islamic education, promoting an understanding of Islamic teachings on ecology within the global sustainability discourse. Novelty: The introduction of the Radical Ideological Ecotheological (EIR) Model and the integration of Islamic ecotheology with the SDGs framework offer a new perspective on how radical movements politicize Islamic teachings on ecology.